State pension and labour market dynamics in South Africa - Geel, Katherine (School of Economics, 2023)
State pensions in South Africa are characterised by their generosity. The current level is approximately double the median per capita income of Africans in 1993. It is possible that pension receipt in a household could have a strong effect on labour market outcomes. This paper investigates the effects of access to pension income on labour supply and employment probability, The large negative elasticity of labour supply to pension income found in Bertrand, Mullainathan and Miller (2003) is much reduced, although the employment probability elasticity has increased in size. Eligible households are characterised by larger household size, higher unemployment levels, lower numbers of prime age workers present in the household, and on average younger members. These patterns tie in with our hypothesis that pension income is used to fund migration and job search, and thus a true picture of the effect of pension payments on labour supply must take this into account, We also investigate the effect of membership of a social network on employment probability. We find that network membership enables individuals to overcome the negative effect of pension income on employment probability.